A chromosome scale assembly of the tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), genome - O. P. Perera; Surya Saha; James Glover; Katherine A. Parys; K. Clint Allen; Snejana Grozeva; Ryan Kurtz; Gadi V. P. Reddy; J. Spencer Johnston; Mark Daly; Thomas Swale (BMC Research Notes, 2023)
Abstract Objective The tarnished plant bug (TPB), Lygus lineolaris (Palisot de Beauvois) (Hemiptera: Miridae), is a pest damaging many cultivated crops in North America. Although partial transcriptome data are available for this pest, a genome assembly was not available for this species. This assembly of a high-quality chromosome-length genome of TPB is aimed to develop the genetic resources that can provide the foundation required for advancing research on this species. Results The initial genome of TPB assembled with paired-end nucleotide sequences generated with Illumina technology was scaffolded with Illumina HiseqX reads generated from a proximity ligated (HiC) library to obtain a high-quality genome assembly. The final assembly contained 3963 scaffolds longer than 1 kbp to yield a genome of 599.96 Mbp. The N50 of the TPB genome assembly was 35.64 Mbp and 98.68% of the genome was assembled into 17 scaffolds larger than 1 Mbp. This megabase scaffold number is the same as the number of chromosomes observed in karyotyping of this insect. The TPB genome is known to have high repetitive DNA content, and the reduced assembled genome size compared to flowcytometric estimates of approximately 860 Mbp may be due to the collapsed assembly of highly similar regions.